2023
DOI: 10.1155/2023/4040504
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Coculture of Primary Human Cells to Analyze Angiogenesis, Osteogenesis, and the Inflammatory Response to Newly Developed Osteosynthesis Material for Pediatric Maxillofacial Traumatology: A Potential Pretesting Model before In Vivo Experiments

Eva Dohle,
Tatjana Fecht,
Tobias Wolfram
et al.

Abstract: During the present study, an in vitro coculture bone tissue mimic based on primary osteoblasts and primary endothelial cells was used for a complex and broad evaluation of a newly developed material for applications in pediatric maxillofacial traumatology. The biomaterial was composed of PDLLA (poly(D,L-lactide)) in various combinations with calcium carbonate (CC), magnesium (Mg), and chitosan (CH). Besides classical biocompatibility analyses, the present study evaluated material-dependent effects on fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Dohle et al recently reported on in vitro investigations of the PDLLA + CaCO 3 blend using primary osteoblasts, primary endothelial cells, and primary dermal fibroblasts. For all three cell types, they observed high cell viability as well as excellent cell adhesion and expression of their typical markers in contact with the sample surface [30]-these cell responses were comparable to the results obtained for PDLLA + CaCO 3 and PDLLA in the present study. For 3D-printed scaffolds of PDLLA + β-TCP, excellent cell attachment, viability, proliferation, and osteogenic differentiation of adipose-derived stem cells seeded on these scaffolds were confirmed by Rezai Rad et al [31].…”
Section: Discussionsupporting
confidence: 89%
“…Dohle et al recently reported on in vitro investigations of the PDLLA + CaCO 3 blend using primary osteoblasts, primary endothelial cells, and primary dermal fibroblasts. For all three cell types, they observed high cell viability as well as excellent cell adhesion and expression of their typical markers in contact with the sample surface [30]-these cell responses were comparable to the results obtained for PDLLA + CaCO 3 and PDLLA in the present study. For 3D-printed scaffolds of PDLLA + β-TCP, excellent cell attachment, viability, proliferation, and osteogenic differentiation of adipose-derived stem cells seeded on these scaffolds were confirmed by Rezai Rad et al [31].…”
Section: Discussionsupporting
confidence: 89%